Diagnostic Performance of Loop-Mediated Isothermal Amplification and Ultrasensitive Rapid Diagnostic Tests for Malaria Screening Among Pregnant Women in Kenya. (11th July 2022) - Samuels, Aaron M; Towett, Oliver; Seda, Brian; Wiegand, Ryan E; Otieno, Kephas; Chomba, Miriam; Lucchi, Naomi; Ljolje, Dragan; Schneider, Kammerle; Walker, Patrick G T; Kwambai, Titus K; Slutsker, Laurence; et al.
Abstract: Background: Screen-and-treat strategies with sensitive diagnostic tests may reduce malaria-associated adverse pregnancy outcomes. We conducted a diagnostic accuracy study to evaluate new point-of-care tests to screen pregnant women for malaria at their first antenatal visit in western Kenya. Methods: Consecutively women were tested for Plasmodium infection by expert microscopy, conventional rapid diagnostic test (cRDT), ultra sensitive RDT (usRDT), and loop-mediated isothermal amplification (LAMP). Photoinduced electron-transfer polymerase chain reaction (PET-PCR) served as the reference standard. Diagnostic performance was calculated and modelled at low parasite densities. Results: Between May and September 2018, 172 of 482 screened participants (35.7%) were PET-PCR positive. Relative to PET-PCR, expert microscopy was least sensitive (40.1%; 95% confidence interval [CI], 32.7%–47.9%), followed by cRDT (49.4%; 95% CI, 41.7%–57.1), usRDT (54.7%; 95% CI, 46.9%–62.2%), and LAMP (68.6%; 95% CI, 61.1%–75.5%). Test sensitivities were comparable in febrile women (n = 90). Among afebrile women (n = 392), the geometric-mean parasite density was 29 parasites/µL and LAMP (sensitivity = 61.9%) and usRDT (43.2%) detected 1.74 (95% CI, 1.31–2.30) and 1.21 (95% CI, 88–2.21) more infections than cRDT (35.6%). Per our model, tests performed similarly at densities >200 parasites/µL. At 50 parasites/µL, the sensitivities were 45%, 56%, 62%, and 74% with expert microscopy, cRDT, usRDT, and LAMP, respectively. Conclusions: This first-generation usRDT provided moderate improvement in detecting low-density infections in afebrile pregnant women compared to cRDTs. Abstract : Most pregnant women in sub-Saharan Africa have low parasite densities and are asymptomatic when screened for Plasmodium falciparum at their first antenatal care visit. The first-generation usRDT provide detect 21% more low-density infections in afebrile pregnant women compared to cRDTs.